2005
DOI: 10.1002/chem.200500036
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Spin State Structure of [Fe(chloroethyltetrazole)6](BF4)2 Obtained from Synchrotron Powder Diffraction Data

Abstract: The complex [Fe(teec)6](BF4)2 (teec = chloroethyltetrazole) shows a two-step complete spin-crossover transition in the temperature range 300-90 K. Time-resolved synchrotron powder diffraction experiments have been carried out in this temperature range, and crystal structure models have been obtained from the powder patterns by using the parallel tempering technique. Of these models, the low-spin state structure at 90 K has been refined completely with Rietveld refinement. Its structural characteristics are dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 48 publications
(62 reference statements)
0
16
0
Order By: Relevance
“…The N···HÀC bonds (Table 6) are rather long compared to those in the tetrafluoroborate com- plex. [24] From the N···H distances it can be concluded that, just as in the case of the tetrafluoroborate complex, at 300 K more N···HÀC hydrogen-bond stabilization exists than at 90 K. Actually, at 90 K two of the three N···H distances are too long to be considered as hydrogen bonds.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…The N···HÀC bonds (Table 6) are rather long compared to those in the tetrafluoroborate com- plex. [24] From the N···H distances it can be concluded that, just as in the case of the tetrafluoroborate complex, at 300 K more N···HÀC hydrogen-bond stabilization exists than at 90 K. Actually, at 90 K two of the three N···H distances are too long to be considered as hydrogen bonds.…”
Section: Resultsmentioning
confidence: 95%
“…[22][23][24] Table 1 lists unit-cell data while the unit-cell volume as a function of temperature is shown in Figure 3 together with the Imaging-Plate data of the scan measurements and the magnetic susceptibility versus temperature (T› = 160-100 K and Tfl = 100-298 K).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations